Транзитивні відображення на топологічних просторах - Білокопитов, Є.; Коляда, С.Ф. (Український математичний журнал, 2013)
Рассматривается классическая проблема топологической динамики — существование неэквивалентных определений топологической транзитивности, в частности условие на динамическую систему, которое следует из всех имеющихся определений. Полная классификация таких динамических систем является основным результатом данной работы. In the present paper, we consider the problem of existence of nonequivalent definitions of topological transitivity, which is a classical problem of the topological dynamics. In particular, we use the fact that all available definitions of this kind imply a condition imposed on the dynamical system. The main result of our investigations is the complete classification of these dynamical systems.